Processing apple pomace powder to reduce environmental pollution - M. M. Zheplinska; V. P. Vasyliv; N. M. Zubar; Z. A. Burova; R. M. Mukoid (Regulatory Mechanisms in Biosystems, 2025)
Apple pomace is a polluting waste and is unsuitable for feeding livestock. Various alternative solutions for the use of apple pomace when implemented in practical conditions can contribute to the development of a technological chain of waste-free apple processing. The by-product – apple pomace – is rich in valuable fiber in the form of pectin substances. Therefore, their processing is of great importance for environmental protection. The paper presents a comparative co n tent of pectin in various plant raw materials and the chemical composition of pectin and the elemental composition of pectin powder in apple pomace, which allows these wastes to be used as an ingredient in the production of food products, in particular in the meat and soft drink industries to reduce the amount of sugar and increase the biological value of the product. The article shows the possibility of using pectin for the production of edible film to protect food products, ant i microbial biofilms, nanoparticles, etc., which extends the shelf life of food. Advances in the use of different extraction sources and knowledge of structural modification have significantly expanded the properties, yield and applications of pectic substances found in apple pomace. Modified pectin has shown better functional properties than native pectin. It has been established that pectin can be used in biomedicine as a targeted application in the delivery of bioactive drugs and to stop the spread of cancer cells in the lungs. During the review of literature sources, the possibility of using apple pomace in the production of bioethanol was considered, which will positively affect environmental processes in the future. The obtained data contain practical value regarding the possibility of waste-free processing of apple pomace in various sectors of the national economy, which is currently a relevant issue.